Republic of San Marino : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Selected Issues paper presents scenarios to assess debt dynamics and discusses key considerations in developing a medium-term fiscal strategy and adjustments.in San Marino. San Marino faces new fiscal challenges. Recent interventions in the financial sector are set to increase the debt to gross domestic product (GDP) level, although the eventual level of public debt remains highly uncertain. The government has granted banks the right to convert tax credits to government bonds, thus creating contingent liabilities. Going forward a fiscal strategy is needed. The scenario analysis in this paper suggests that the debt-to-GDP ratio could rise to 55-90 percent of GDP. Such levels would be high for San Marino and well above the level observed in other European microstates. At the same time, government deposits have been decreasing to a low level. A medium-term fiscal strategy could thus aim at containing the debt-to-GDP ratio and rebuilding deposits. The analysis in this paper offered considerations that could be helpful in determining fiscal adjustments needed to reach such targets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet